Four letters flow together: Words to the Yabás (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article, crafted by the hands of four artists involved in the research and creation process of Mar Aberto: confluências de vida e arte entre mulheres das águas, started from the premise that writing about healing would only make sense if this was in itself a healing process. Grounded in this idea, the letter was chosen as a format for bringing the tone of intimacy and multiplicity to the voices of the authors who delivered their words as offerings to the four great mothers in African-based religions: the Yabás Nanã, Oxum, Iansã e Iemanjá. As a part of the artistic and research process about women who work with artisanal fishing in Santa Catarina, the Yabás feminine strength emerges as a prayer for transmutation and creation. During these shared journeys of healing and creativity will flow together questions about the body, artistic practices and the process experienced so far.
Keywords: Waters; Healing; Yabás; Female artists; Performance